Pastoralny wymiar prawa kanonicznego. Uwagi na kanwie przemówień do Roty Rzymskiej z 2006 i 2011 roku - Pastwa, Andrzej (Studia Pastoralne, 2026)
The main point of the article is the aspectual attempt at answering the question of how defining the aim of the canon law (theological justification of ius Ecclesiae) can result in its substantial and adequate use. The background of the scholarly contemplation are Benedict XVI’s addresses to the Tribunal of the Roman Rota of 2006 and 2011. The cognition of enunciations contained in those addresses gives the basis for the exploration of some crucial matters: What does such a firmly articulated magisterial indication that the ecclesiology of the Lumen Gentium Dogmatic Constitution on the Church plays an irreplaceable role in the appropriate interpretation and application of law mean? What intention does that firm, as for the Post-Second Vatican Council time, emphasis on the pastoral dimension of the canon law by the church legislator entail? Authentic pastoral sensibility, which the mentioned-above Pope’s addresses authoritatively treat about, reveals itself in the pastoral solicitude to prevent nullity of a marriage at the time such a marriage contract is approved of, as well as in judicial defense and promotion of the truth about the human person and marital/family-oriented communio personarum. The clou of those issues is well reflected in the words of Benedict XVI: „it is necessary to encourage in all sectors, and in a particular way in the field of marriage and of the family, a positive dynamic, sign of profound harmony between the pastoral and the juridical which will certainly prove fruitful in the service rendered to those who are approaching marriage” (Address to the Roman Rota, Jan. 22, 2011).